A Study On The Effect Of Feng Shui Interest On Feng Shui Recognition Of Location And Management Performance: With Small Businesses As Subject - Yeon-Su, Park (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of this study is to derive the main factors of Feng Shui site recognition and the effect of the factors on the Management Performance of small business through the previous studies in order to investigate the relationship between Feng Shui interest and management performance for the sake of development of small businesses. In addition, the research is directed to the mediating effect of Feng Shui site recognition and adjusted mediating effect of entrepreneurship in the relationship between Feng Shui interest and management performance. First, the verification of the hypothesis, 'Feng Shui interest will have a positive influence on the Feng Shui site recognition', showed that Feng Shui interest had a positive influence on all the space placement, space shape, junction space, and topography. Second, the verification of the hypothesis, 'Feng Shui site recognition will have a positive effect on management performance', showed that Feng Shui site recognition had a positive effect on characteristics of Feng Shui site recognition such as space placement, junction space and topography, but not on space shape. Third, the verification of the hypothesis, 'Feng Shui site recognition will mediate the influence of Feng Shui interest has on management performance', showed that Feng Shui site recognition had a positive effect on characteristics of Feng Shui site recognition such as space placement, junction space and topography, but statistically not significant on space shape. Fourth, the verification of the hypothesis, 'innovation will control the mediating effect of Feng Shui site recognition in the path that Feng Shui interest affects management performance through Feng Shui site recognition', showed that innovation controlled the mediating effect. It is necessary not to confine the subject of research to small businesses, but to extend it to medium- or large-sized companies. In addition, it is necessary to research the impact of Feng Shui site recognition not only on the management field but also on other fields.